The Use of Captional Videos Strategy to Improve Students' Vocabulary Mastery - Ilma, Firda; Mafulah, Siti (Universitas Islam Balitar, 2024)
The aim of this study is to investigate how captional videos strategy as a teaching media improve students' vocabulary. Classroom Action Research (CAR) was used in this study. There were 32 students of eighth grade of junior high school as participants. The instruments used were test, observation checklist, and questionnaire. Criteria of success, lesson plan, media used was set on planning. The step was followed by implementing, obserning, and reflecting. This study was done on two cycles since the result of the first cycle did not meet the criteria of success. The result shows that vocabulary test result in Cycle II passed the criteria of success. Out of 32 students, 86% of the students got scores above 75, and 75% of students were active in the class. This suggests that including captioned movies into the classroom may be a useful way to expand students' lexical knowledge and proficiency in English. Therefore, it is suggested for teacher to use captional video as alternative media in teaching English especially in improving studdents’ vocabulary.